Kaderisasi Duta Stunting Bagi Majelis Jemaat dalam Mencegah Anak Stunting di Gereja Protestan Persektuan Tapian Nauli - Erman Saragih; Tiffany Tamba; Junjungan Simorangkir; Megawati Manullang; Warseto Sihombing; Ofertiaman Zai; Rut Hutabarat; Helma Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
Stunting is a serious health problem in Indonesia, including in the North Tapanuli region, North Sumatra Province. The root cause of stunting is a lack of understanding of the root causes of stunting itself. This problem is certainly not limited to the task of the Ministry of Health alone, but the existence of the church is very strategic and important for service integration and collaboration. The purpose of this PkM activity is to conduct stunting ambassador cadre formation within the scope of church workers. The ambassadors are given the burden of understanding the root causes of stunting, education on forms of church service related to stunting education, and stunting ambassador cadre formation to the GPP Tapian Nauli Congregation Assembly. The church has an important role in helping to eradicate stunting in North Tapanuli. The church can be a forum for providing education and coaching to congregation members about the importance of balanced nutrition-maternal and child health.